Statement on the safety of d‐ribose. (13th December 2018) - ,; Turck, Dominique; Castenmiller, Jacqueline; De Henauw, Stefaan; Hirsch‐Ernst, Karen Ildico; Kearney, John; Knutsen, Helle Katrine; Maciuk, Alexandre; Mangelsdorf, Inge; McArdle, Harry J; Naska, Androniki; Pelaez, Carmen; et al.
Abstract: In 2018, the EFSA NDA Panel adopted the Scientific Opinion on the safety of d ‐ribose as a novel food pursuant to Regulation (EU) 2015/2283 when used in a variety of food, concluding that d ‐ribose is safe for the general population at intake levels up to 36 mg/kg body weight (bw) per day, but that its safety at the intended uses and use levels as proposed by the applicant could not be established. Following a request from the European Commission, the EFSA NDA Panel was asked to carry out a supplementary safety assessment for d ‐ribose by considering the new proposed uses and use levels submitted by the applicant. In order to address the present mandate, an intake assessment was carried out based on individual data from the EFSA Comprehensive European Food Consumption Database. Intakes were estimated for all age groups of the general population. The resulting ranges for the mean and high‐level estimated intakes of d ‐ribose for all the population groups, including the target population groups, did not exceed the acceptable level of intake for the general population previously defined, i.e. 36 mg/kg bw per day, except for one survey on adolescents where the mean and 95th percentile of the intake estimates were 8.6 and 39.4 mg/kg bw per day, respectively. The Panel concludes that the novel food, d ‐ribose, is safe under the new proposed conditions of use.